Angiogenesis in Ischemic Disease - Marti, Hugo H.; Risau, Werner (Thrombosis and Haemostasis, 1999)
Angiogenic growth factors and their endothelial receptors function as major regulators of blood vessel formation. The VEGF/VEGFR and the Angiopoietin/Tie2 receptor systems represent key signal transduction pathways involved in the regulation of embryonic vascular development. Inactivation of any of the genes encoding these molecules results in defective vascular development and lethality between embryonic day 8.5 and 12.5. In addition, VEGF and its receptors are also critically involved in the regulation of pathological blood vessel growth in the adult during various angiogenesis-dependent diseases that are associated with tissue hypoxia, such as solid tumor growth and ischemic diseases. It is now well established that therapeutic angiogenesis can be achieved in animal models of hind limb and myocardial ischemia by exogenously adding VEGF and/or other angiogenic growth factors. Available clinical data from human trials also suggests that patients with severe cardiovascular diseases could potentially benefit from such therapies. However, much more work needs to be done to compare the potency of different angiogenic factors or the combination thereof, as well as the best way of delivery, either as recombinant proteins, as naked DNA or via adenoviral vectors. Nevertheless, the therapeutic efficacy of simply injecting naked plasmid DNA or proteins into ischemic tissue to deliver secreted angiogenic factors is an encouraging finding. Time will show whether the adverse side effects of therapeutic angiogenesis, mainly vascular permeability and edema formation, can be minimized and angiogenic factors can be used as an effective therapy in patients for the treatment of ischemic diseases such as arterial occlusive disease, myocardial infarction, and, eventually, also stroke.
Keywords: Ischemia; therapeutic angiogenesis; VEGF; angiopoietin; hypoxia; HIF-1; stroke; myocardial infarction